Drawing the Holocaust : a teenager's memory of Terezin, Birkenau, and Mauthausen - Kraus, Michal, 1930- (Hebrew Union College Press, University of Pittsburgh Press, 2016)
"Twelve-year-old Michael Kraus began keeping a diary while he was still living at home in the Czech city of Nachod but continued writing while a prisoner at Theresienstadt (Terezín). When he was shipped with other prisoners to the death camp at Auschwitz-Birkenau, all of his writings were confiscated and destroyed. After his liberation and while convalescing, he began to draw and make notes again about his experiences in Theresienstadt, in Auschwitz, the first death march out of Mauthausen, and its satellite camps, in Melk and Gunskirchen. As a teenager confronting the traumas of these experiences, Kraus found that recording his memories in words and pictures helped him overcome his hatred for those who had murdered his parents. The process of writing and drawing also helped him begin the painful transition to a so-called normal life. As a survivor, Kraus also felt the need to recount his experiences for the benefit of future generations, especially on behalf of the many who did not survive. The present edition makes this memoir, originally written in Czech and significant for having been written so close to the author's liberation, widely available to English readers for the first time. It also reproduces pages from the original booklets that show how the teenage Kraus illustrated his memories with pencil drawings that both complement and extend his story, giving readers a sense of its character as an unusual and important historical document"--